Smart short-chain bifunctional N, N-dimethylethanolamine for high-performance lithium batteries. (20th August 2018) - Fan, Xiaojing; Xing, Aiming; Sun, Wenwei; Lu, Ruifeng; Li, An; Wei, Xiangfeng; Meng, Fancheng; Liu, Jiehua
Abstract: Li metal batteries have attracted many attentions owing to their excellent nature, including easier processes and higher energy density than that of conventional Li-ion batteries. However, lithium whiskers often result in the instability of Li anode and electrolyte, and even short circuit, which hinders the safe application of lithium batteries. In this paper, N, N-dimethylethanolamine (DMEA) is employed as a short-chain bifunctional organic additive to save the above problem in Li||LiCoO2 batteries. DMEA not only effectively restrains the growth of Li whiskers by hydroxyl groups and decreases the concentration of free HF by amine groups, but also forms new high ionic-conductivity DMEA-Li based SEI film rather than only hard LiF SEI layer. As a result, the rate performance and capacity of Li||LiCoO2 batteries have been remarkably improved, owing to the participation of bifunctional DMEA. The capacity of 159 mA h g −1 has been retained after 150 cycles with a low capacity fading of 0.07 mA h g −1 per cycle, 43% higher than that of DMEA-free cells at 0.5 C. Graphical abstract: Image 1 Highlights: DMEA could effectively restrain the growth of Li whiskers by alcohol groups. DMEA decreases the concentration of free HF by amine groups. A high ionic-conductivity smart DMEA-Li SEI layer has been studied. DMEA-Li cells markedly improve the electrochemical performance of Li||LiCoO2 cells.